Prefilled pen versus prefilled syringe: a pilot study evaluating two different methods of methotrexate subcutaneous injection in patients with JIA - Roszkiewicz, Justyna (Pediatr Rheumatol Online J, 2020)
BACKGROUND: Methotrexate is the most commonly used disease-modifying antirheumatic drug recommended in the treatment of juvenile idiopathic arthritis. It can be administered orally or subcutaneously, the latter method is associated with fewer side effects and higher drug bioavailability. Nevertheless, the pain associated with injection is a considerable drawback of this treatment option in the pediatric population. Currently, there are two single-use subcutaneous injection devices available: the prefilled syringe and the prefilled pen. This prospective, two-sequence crossover study aimed to compare ease of use, frequency of therapy side effects, injection-site pain and parent/patient preference of those methotrexate parenteral delivery systems. METHODS: Twenty-three patients with juvenile idiopathic arthritis, already treated with subcutaneous methotrexate in the form of prefilled syringe in the period October 2018 – April 2019 completed a questionnaire evaluating their experience with this device. Subsequently, children received a one-month supply of pen autoinjector and completed the same questionnaire, regarding their experience with the new methotrexate delivery system. If the patient was not performing the injections himself the questionnaires were completed by the caregiver administrating MTX. The results obtained in both questionnaires were compared using the Wilcoxon matched-pairs signed-rank test. RESULTS: 82,6% patients and their caregivers voted for the prefilled pen as their preferred method of subcutaneous methotrexate administration. Moreover, the injection with the prefilled pen was reported as less painful in comparison to the prefilled syringe (p < 0.01). Side effects of methotrexate were less pronounced after the prefilled pen treatment, this difference was most prominent regarding gastrointestinal adverse events associated with the injection (p < 0.01). CONCLUSION: Administration of methotrexate using the pen device is a promising way of subcutaneous methotrexate delivery in children with juvenile idiopathic arthritis, as the injection is less painful and associated with fewer side effects.